Biosensors in Endocrinology- Review Article - Farnoush FARIDBOD; Mohammad Reza GANJALI; Bagher LARIJANI; Parviz NOROUZI; Morteza HOSSEINI (Tehran University of Medical Sciences, 2015)
Biosensors are classes of sensors in which at least a biological process is used in sensing procedure. They are generally composed of three parts: a sensing element, a transducer, and a signal processor (or detector). They can be categorized by type of sensing materials or by detection techniques. From their invention time up to now, various biological species have been analyzed using variety of biosensors. They have been widely used for environmental, industrial, pharmaceutical and clinical applications in many research papers. Perhaps the number of biosensors which had a chance to commercialize and enter to the market is limited, but by recent developments in science and technology, day-by-day, the number of commercial biosensors are growing. Their importance in clinical medicine can be found in determination of biomarkers for early diagnosis of disease or for control and manage of them in point-of-care devices. Diagnosis and control of many endocrine diseases and metabolic disorders depend strongly on determination of chemicals, hormones and antibodies. A large number of biosensors research studies have focused on determination of these biomolecules. One of the famous commercial biosensor is widely used in management of diabetes is glucometer. They are portable commercial biosensors which measure the amount of glucose in a blood drop. The main challenges in designing biosensors are decrease the limit of detection, increasing the sensitivity and accuracy in an analysis, increasing lifetime and miniaturization. Even scientists are now trying to develop biosensors for non-invasive measurements of biomarkers in saliva or tears.   Keywords: Biosensor, Endocrinology, Point-of-care device, Diabetes, Glucometer